Analysis of Violations of the Code of Ethics for Professional Accountants in the Business Sector: Case Study of AP and KAP Involvement at PT Asuransi Adisarana Wanaartha (WAL) - Anggiria, Kristanti Srika; Trisnaningsih , Sri (Universitas Wiralodra, 2023)
The research aims to analyze violations of the professional code of ethics for accountants in the business sector, focusing on the case study of PT Asuransi Adisarana Wanaartha Life (WAL) to obtain a comprehensive review. Hopefully, this study will open new insights into the role of codes of ethics in maintaining the integrity and trust of the public in the accounting profession and the public accounting profession. This research uses a literature review analysis method. The type of data collection used is secondary data in the form of journal articles with index Sinta 2 - 6, Garuda, index Copernicus international (ICI) via the page https://scholar.google.com over five years from 2019 -2023, as well as news and press releases via the website. The data analysis technique is conducted descriptively by analyzing and identifying scientific articles, news, and press releases, generating a more informative summary. The results of the research reveal how important it is for every practitioner to maintain competence and expertise in the field of accounting, adhere firmly to and comply with the code of ethics of the accounting profession in carrying out accounting practices, thus creating a professional and accountable attitude, and avoiding the risk of violating the code of ethics of the accounting profession.